Prespektif Calon Guru PAI dalam Membentuk Perkembangan Siswa dengan Guru BK - Ummah Karimah; Siti Shofiyah; Karans Raja Bombay; Musthofa Al Anshory; Faidah Al Anshory; Hafizh Taufiqurrohman (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to determine the perspective of prospective PAI teachers in shaping student development with BK teachers. This research is a qualitative descriptive study. The subjects of this study were students of Islamic Religious Education. The method of data collection in this research interviews. The results of the study found that as prospective teachers who have received Counseling Guidance courses in general, as prospective teachers of Islamic Religious Education, it is very important to always ask the students' progress to the Counseling Guidance teacher. It is very important for prospective Islamic Religious Education teachers to find out about the development of their students to the Guidance Counseling teacher because the Guidance Counseling teacher understands more deeply the behavior of a student. By knowing the development of students, an Islamic Religious Education teacher can find out how the character of the students he teaches, by knowing how the character of the students is, the teacher can more easily determine the right methods and strategies and are easily accessible to students. The partnership between Islamic Religious Education (PAI) teachers and Counseling Guidance (BK) teachers is one of the national education programs.